Being Indigenous in Jim Crow Virginia : Powhatan People and the Color Line - Feller, Laura J. (Laura Janet); Project Muse. (Norman : University of Oklahoma Press, 2022)
"Explores experiences and strategies of tidewater Virginia Indians, descendants of peoples of the seventeenth-century Algonquian Powhatan chiefdom, in maintaining, creating, and re-creating their identities as Native Americans from the 1850s through the Jim Crow era. Examines how tidewater Native individuals, families, and communities positioned themselves as red people, rather than Black or white, in an era when some white Virginians argued that Virginia's Indians were 'mulattoes' and 'colored people.'"--
"A Home in a Strange Land" -- Virginia's 1924 "Racial Integrity" Law -- Constructing Native Identities, 1865 to 1931 -- White Ethnographers and Salvage Ethnography -- The Aftermath of the "Racial Integrity" Law, 1930s to 1950s.
Description based on print version record.
Keywords: Race relations; Powhatan Indians; Powhatan (Indiens) -- Histoire -- 20e siecle; Powhatan (Indiens) -- Histoire -- 19e siecle; Powhatan (Indiens) -- Identite ethnique; Powhatan Indians -- History -- 20th century; Powhatan Indians -- History -- 19th century; Powhatan Indians -- Race identity; Virginia -- Tidewater (Region); Tidewater (Virg. : Region) -- Relations raciales; Tidewater (Va. : Region) -- Race relations; History; Electronic books